Cardiometabolic characterization in metabolic dysfunction–associated fatty liver disease - Perdomo, Carolina M.; Núñez-Córdoba, Jorge M.; Ezponda, Ana; Mendoza, Francisco J.; Ampuero, Javier; Bastarrika, Gorka; Frühbeck, Gema; Escalada, Javier (Frontiers in Medicine, 2022)
Background. To better understand the patient’s heterogeneity in fatty liver disease (FLD), metabolic dysfunction–associated fatty liver disease (MAFLD) was proposed by international experts as a new nomenclature for nonalcoholic fatty liver disease (NAFLD). We aimed to evaluate the cardiovascular risk, assessed through coronary artery calcium (CAC) and epicardial adipose tissue (EAT), of patients without FLD and patients with FLD and its different subtypes. Methods. Cross sectional study of 370 patients. Patients with FLD were divided into 4 groups: FLD without metabolic dysfunction (non-MD FLD), MAFLD and the presence of overweight/obesity (MAFLD-OW), MAFLD and the presence of two metabolic abnormalities (MAFLD-MD) and MAFLD and the presence of T2D (MAFLD-T2D). MAFLD-OW included two subgroups: metabolically healthy obesity (MHO) and metabolically unhealthy obesity (MUHO). The patients without FLD were divided into 2 groups: patients without FLD and without MD (Non-FLD nor MD) and patients without FLD but with MD (Non-FLD with MD). EAT and CAC (measured through the Agatston Score) were determined by computed tomography. Results. Compared with Non-FLD nor MD subgroup of patients: regarding EAT, patients with MAFLD-T2D and MAFLD-MUHO had the highest risk for CVD (OR 14.95, 95% CI 4.02–55.66 and OR 16.9, 95% CI 6.46-44.25, respectively). MAFLD-MHO and Non FLD-MD were also at risk for CVD (OR 3.51, 95% CI 1.77-6.93 and OR 3.47, 95% CI 1.66-7.25, respectively). Non MD-FLD did not have a significantly increased risk compared with patients without FLD (1.89; 95% CI, 0.70-5.09). Regarding CAC, patients with MAFLD-T2D had a significant increased risk for CVD compared with patients without FLD nor MD (OR 6.13, 95% CI 2.06-18.2). MAFLD-MUHO, MAFLD-MHO, Non MD-FLD and Non-FLD with MD did not have significantly increased risk compared with patients without FLD nor MD (OR 2.36, 95% CI 0.85-6.52; OR 1.72, 95% CI 0.64-4.65; OR 2.19, 95% CI 0.47-10.15 and OR 1.42, 95% CI, 0.45-4.42, respectively). Conclusions. MAFLD–T2D and MAFLD–MUHO phenotypes had a significant risk for CVD. MAFLD new criteria reinforced the importance of identifying metabolic phenotypes in populations, as it may help to identify patients with higher CVD risk and offer a personalized therapeutic management in a primary prevention setting.